Smartphone use and its addiction among Jammu adolescents - Dogra, Nupur; Sharma, Shaveta (Indian Journal of Community Health, 2024)
Background: Smartphones play a crucial role in our everyday life. Smartphones help users to develop social connections with others, gain information and entertain themselves through various applications. With the widespread use of smartphone, the number of smartphone users has been increasing worldwide. As smartphones are getting popular, smartphone addiction has become a serious mental health problem among adolescents. Objectives: To find out significant differences in smartphone addiction among adolescents with respect to their gender and locale. Methodology: Descriptive survey method was used for conducting the study. The sample consists of 200 adolescents of government and private schools from Jammu and Kathua. ‘Smartphone Addiction Scale’ (2021) developed by Vijayshri and Masaud Ansari was used for data collection. Results: It was found that smartphone addiction was significantly higher among female adolescents (M=65.34) as compared to their male counterparts (58.61). Further, it was also found that smartphone addiction was significantly higher in urban adolescents (M=64.37) than rural adolescents (M=59.08). Conclusion: In order to combat smartphone addiction among adolescents, we advise the creation of healthy environment at the family and school levels. Teachers should provide knowledge to the students about smartphone security tips and educational programmes should be organized for protecting psychological well-being of the adolescents.